The relationship between liquidity and profitability in the automotive industry: a comparison between the electric car market and the traditional/hybrid market - Girão, José Maria Santos (2021)
This Work Project clarifies the relationship between liquidity and profitability, proxied by Return on Assets(ROA).Relying on data retrieved from the consolidated financial statements from the major traditional and electric players in the market, for the years 2015-2019, a negative relationship between the quick ratio and ROA was found in the traditional market and a positive one in the electric market. Cash Conversion Cycle is longer in the traditional market, however ROA shows a negative relationship with DIO and positive with DPO, for both markets. Thus, managers can increase ROA by reducing inventories or increasing the duration of payments.